2017
DOI: 10.5455/jice.20170327073745
|View full text |Cite
|
Sign up to set email alerts
|

A Synergistic effect of artocarpanone from Artocarpus heterophyllus Lam. (Moraceae) on the antibacterial activity of some antibiotics and their effect on membrane permeability

Abstract: Aim/Backgrounds:Artocarpanone isolated from Artocarpus heterophyllus L. (Moraceae) exhibits antibacterial activity. The present study investigated synergistic activity between artocarpanone and tetracycline, ampicillin, and norfloxacin, respectively, against methicillin-resistant Staphylococcus aureus (MRSA), Pseudomonas aeruginosa, and Escherichia coli.Materials and Methods:A broth microdilution method was used for evaluating antibacterial susceptibility. Synergistic effects were identified using a checkerboa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The loss of 260 nm intracellular material was detected using a UV-Vis spectrophotometer (Zhou et al 2008;Septama et al 2017). Overnight cultures of bacteria were washed with normal saline and resuspended in normal saline.…”
mentioning
confidence: 99%
“…The loss of 260 nm intracellular material was detected using a UV-Vis spectrophotometer (Zhou et al 2008;Septama et al 2017). Overnight cultures of bacteria were washed with normal saline and resuspended in normal saline.…”
mentioning
confidence: 99%
“…Study by Cushnie and Lamb showed that galangin induced the cytoplasmic membrane damage in Staphylococcus aureus (Cushnie and Lamb, 2005). In addition, quercetin also performed strong antibacterial activity against E. coli by increasing inner membrane permeability and dissipation of the membrane potential (Simoes et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Artocarpanone at 2 × MIC and MIC only inhibited the bacterial growth after 24 h incubation. It has been reported that artocarpanone had satisfactory antibacterial activity against several bacteria including E. coli (Septama and Panichayupakaranant, 2015).This compound also enhanced the antibacterial activity of norfloxacin by altering membrane permeability of MRSA (Septama et al, 2017). It has been known the Gram-negative bacteria are surrounded by outer membrane which providesa selective barrier to protect the cell from harmful agents (Lambert, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The samples were then incubated at 30 °C for 60 min. Afterwards, the cell suspension was centrifuged at 13,500× g for 15 min, and the OD at 260 nm of the supernatant was measured [ 39 , 40 ]. The released UV-absorbing materials were represented by the mean values ± SD by measuring three independent replicates.…”
Section: Methodsmentioning
confidence: 99%